Memory and History: A Comparison of the Past in Slovak Prose of the Post-2000 Period - Barborík, Vladimír (Porównania, 2021)
This study focuses on how two kinds of memory: historical and personal are reflected in a section of Slovak literature of the past two decades. A variety of autobiographical genres and biographically-stylised fictional prose draw on personal memory, and history, is the domain of historical genres, particularly the novel. After the 1990s, the present was deemed important and historical presentations of the past were parodied in the prose of Peter Pišťanek and Igor Otčenáš. At the beginning of the new millennium, however, prose portraying and reflecting on the past reappeared. Memory- based writing which is concerned with an individual situated within history, or outside of it, is more persuasive. Memory-based writing is used in different forms of autobiographical writing: within fiction it takes a form of biographical stylisation (e. g. Vilikovský, Kopcsay and Rozner). In the past ten to fifteen years, there has been a renewed interest in history in Slovak literature, mainly in pre-1989 history (e. g. Rankov, Krištúfek and Lavrík), which had been mistreated in pre-1989 Slovak literature, and later there was no interest in it or it was even rejected in the 1990s. During that time, historical memory was exploited to meet societal requirement. Silvester Lavrík was an exception—he was able to marry the two basic approaches to the past (personal history and historical) in a form of a dispute between them.